Reactions of the subunits of the class II major histocompatibility complex molecule IAd. - Tampé, R (1991)
Major histocompatibility complex (MHC) class II molecules are heterodimers formed by noncovalent linkage of alpha and beta chains. It has been shown that the subunits of the MHC class II molecules IAd and IEk bind antigenic peptides as well as antigenic peptides labeled with fluorescent probes. Laser scanning fluorescence microscopy on SDS/polyacrylamide gels demonstrates that the subunit-peptide complexes of IAd are stable over a wide pH range. Below pH 5.3 the heterodimer of IAd dissociates into the free chains, which still bind antigenic peptides such as the 18-amino acid peptide obtained by a tyrosine addition to a chicken ovalbumin peptide, Ova-(323-339)Y. The stability of preformed subunit complexes with fluorescein-labeled Ova-(323-339)Y was investigated by using high-performance size exclusion chromatography and epifluorescence microscopy. Each subunit forms a long-lived complex, both in detergent solutions and in reconstituted lipid bilayers. At 37 degrees C and pH 7.0 the dissociation half-time of the beta-subunit-peptide complex was determined to be 28 hr and that of the alpha-subunit-peptide complex was 10 hr. In contrast to the dissociation of the peptide from the IAd heterodimer, the half-times for dissociation of the peptide from the separate chains are not decreased at pH 5.0.